Magnesium oxide powder and resin composition using same
By adding MgAl2O4 coating layer to magnesium oxide powder and controlling the particle size, the problem of insufficient moisture resistance and dielectric performance of filler materials in high-frequency band equipment is solved, and excellent moisture resistance and median used in high-frequency band equipment is achieved. Filler material with low tangent of electrical loss.
Patent Information
- Application Number
- CN202380049104.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to provide filler materials with excellent moisture resistance and low dielectric loss tangent in high-frequency band equipment.
By using magnesium oxide core particles containing the MgAl2O4 coating layer as filler, and controlling the value particle size of 25 μm or more and 180 μm or less, the moisture resistance and dielectric properties of magnesium oxide powder are improved.
The filler material used in high-frequency band equipment has excellent moisture resistance and low dielectric loss tangent and maintains good thermal conductivity.
Smart Images

Figure CN119403762A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to magnesium oxide powder and a resin composition using the same. Background Art
[0002] In the field of semiconductor sealing materials, inorganic metal oxide powders such as silica and alumina are used as fillers to improve thermal expansion coefficient, thermal conductivity, flame retardancy, etc. However, the thermal conductivity of silica is low, and although the thermal conductivity of alumina is higher than that of silica, its hardness is also higher, so there is a problem that the equipment used is easily worn. Therefore, it is being explored to use magnesium oxide powder, which has a higher thermal conductivity than silica and alumina and a lower hardness than alumina, as a filler applicable in the above fields.
[0003] It is known that magnesium oxide powder has low moisture resistance and reacts with moisture in the atmosphere to form magnesium hydroxide. If magnesium hydroxide is formed, the thermal conductivity is likely to decrease, so the surface of magnesium oxide powder is coated to improve moisture resistance. For example, Patent Documents 1 and 2 describe that the surface of magnesium oxide powder is coated with aluminum oxide or a composite oxide containing aluminum to improve the moisture resistance of magnesium oxide powder.
[0004] However, in recent years, with the increase in the amount of information communication in the communication field, the use of high-frequency band signals in electronic equipment, communication equipment, etc. is expanding. On the other hand, the use of high-frequency band signals in the aforementioned equipment also causes the problem of increased transmission loss of circuit signals. Therefore, fillers used in high-frequency band equipment require materials with low dielectric loss tangent.
[0005] Prior art
[0006] Patent document 1: Japanese Patent Application Publication No. 63-248716;
[0007] Patent document 2: Japanese Patent No. 4302690. Summary of the invention
[0008] Therefore, an object of the present invention is to provide a magnesium oxide powder (I) having excellent moisture resistance and capable of achieving a low dielectric loss tangent applicable also to high-frequency band devices, and a resin composition using the same.
[0009] As a result of careful studies, the inventors of the present invention have discovered that by providing a magnesium oxide powder comprising coated particles having a surface of a core particle containing magnesium oxide coated with a layer containing a certain amount of MgAl2O4, and by setting the median particle size (D50) of the magnesium oxide powder to be greater than 25 μm and less than 180 μm, a magnesium oxide powder capable of solving all of the above-mentioned technical problems can be obtained, thereby completing the present invention.
[0010] That is, the present invention has the following aspects.
[0011] [1] A magnesium oxide powder (I) comprising coated particles (X), wherein the coated particles (X) are core particles (A) containing magnesium oxide and the surface of the core particles (A) is coated with a coating layer (B) containing MgAl2O4,
[0012] The ratio of MgAl2O4 to the total mass of the magnesium oxide powder (I) is more than 1 mass % and less than 38 mass %,
[0013] The median particle size (Di50) of the magnesium oxide powder (I) is 25 μm or more and 180 μm or less.
[0014] [2] The magnesium oxide powder (I) according to [1], wherein the ratio of periclase to the total mass of the magnesium oxide powder (I) is 80% by mass or more.
[0015] [3] The magnesium oxide powder (I) according to [1] or [2], wherein the average circularity (ARi) of the magnesium oxide powder (I) is 0.75 or more.
[0016] [4] The magnesium oxide powder (I) according to any one of [1] to [3], wherein the magnesium hydroxide content after the test measured under the following conditions is less than 50% by mass.
[0017] <Measurement Conditions>
[0018] 10 g (M1) of magnesium oxide powder (I) was left to stand for 168 hours in a test apparatus at a temperature of 135°C and a humidity of 85 RH%. The mass (M2) of the magnesium oxide powder (I) after standing was measured, and the change in mass before and after standing was substituted into the following formula (1) to calculate the magnesium hydroxide content.
[0019] {(M2-M1) / 18.0}×(40.3 / M1)×100...(1)
[0020] (In formula (1), M1 is the mass (g) of the magnesium oxide powder (I) before standing, M2 is the mass (g) of the magnesium oxide powder (I) after standing, and 18.0 and 40.3 are the molecular weights of H2O and MgO, respectively.)
[0021] [5] The magnesium oxide powder (I) according to any one of [1] to [4], wherein the viscosity measured under the following conditions is 2000 Pa·s / 25°C or less.
[0022] <Measurement Conditions>
[0023] A resin composition composed of 60 volume % of a bisphenol A type liquid epoxy resin (epoxy equivalent: 184-194) and 40 volume % of magnesium oxide powder (I) was subjected to a rotational rheometer at a shear rate of 1.0 / s and a plate shape of a circular flat plate. The viscosity was measured at a sample thickness of 1 mm and a temperature of 25 ± 1 °C.
[0024] [6] The magnesium oxide powder (I) as described in any one of [1] to [5], which is for resin filling.
[0025] [7] A resin composition comprising the magnesium oxide powder (I) according to any one of [1] to [6] and at least one resin selected from thermoplastic resins and thermosetting resins.
[0026] [8] The resin composition according to [7], which is used for a sealing material, a TIM material or a substrate of a high-frequency band device.
[0027] According to the present invention, it is possible to provide a magnesium oxide powder (I) which is excellent in moisture resistance and can achieve a low dielectric loss tangent applicable also to high-frequency band devices, and a resin composition containing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an example of an image obtained by mapping the aluminum component on a cross-sectional image of the magnesium oxide powder (I) of the present invention using a field emission scanning electron microscope (FE-SEM) and energy dispersive X-ray spectroscopy (EDS). DETAILED DESCRIPTION
[0029] Hereinafter, one embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiments and can be implemented with appropriate changes within the scope that does not hinder the effects of the present invention. When a specific description recorded for one embodiment is also applicable to other embodiments, its description is sometimes omitted in other embodiments. The expression "α to β" showing a numerical range in this specification means "above α and below β". In addition, "powder" in this specification means "an aggregate of multiple particles".
[0030] [Magnesium oxide powder (I)]
[0031] The magnesium oxide powder of the present embodiment is a magnesium oxide powder (I), characterized in that the surface of the core particle (A) containing magnesium oxide is coated with a coating layer (B) containing MgAl2O4, wherein the proportion of MgAl2O4 relative to the total mass of the magnesium oxide powder (I) exceeds 1% by mass and is less than 38% by mass, and the median particle size (Di50) of the magnesium oxide powder (I) is greater than 25 μm and less than 180 μm. The magnesium oxide powder (I) of the present embodiment (hereinafter, sometimes only recorded as "powder (I)") has excellent moisture resistance and can achieve a low dielectric loss tangent that can also be used in high-frequency band equipment. In addition, the thermal conductivity of the magnesium oxide powder (I) of the present embodiment is also good. The following describes the details of the magnesium oxide powder (I) of the present embodiment.
[0032] <Coated Particles (X)>
[0033] The powder (I) of this embodiment comprises coated particles (X) whose surfaces are coated with a coating layer (B) containing MgAl2O4 and a core particle (A) containing magnesium oxide. By comprising such coated particles (X), the moisture resistance of the powder (I) is improved.
[0034] (Core particle (A))
[0035] The core particles (A) are particles containing magnesium oxide as a main component. The phrase "containing magnesium oxide as a main component" means that the core particles contain magnesium oxide in an amount exceeding 50% by mass relative to all components (100% by mass) constituting the core particles.
[0036] The core particle (A) may also contain components other than magnesium oxide. As components other than magnesium oxide, alkali components, boron, iron, etc. added when manufacturing magnesium oxide particles can be cited. When the powder (I) of the present embodiment is used as a filler for semiconductor sealing materials, for example, the proportion of magnesium oxide in the core particle (A) is preferably 90% by mass or more, and more preferably 95% by mass or more relative to the total components (100% by mass) constituting the core particle. In addition, particles containing magnesium oxide in such a ratio can be obtained, for example, by methods such as electric melting method and sintering method.
[0037] (Coating layer (B))
[0038] The coated particles (X) contained in the magnesium oxide powder (I) of this embodiment have a coating layer (B) containing MgAl2O4. MgAl2O4 (hereinafter, sometimes also described as "spinel") is a composite oxide of magnesium and aluminum. The coated particles (X) containing the core particles (A) whose surfaces are coated with the coating layer (B) containing spinel can improve the moisture resistance of the powder (I).
[0039] The amount of spinel contained in the powder (I) of the present embodiment is more than 1% by mass and less than 38% by mass relative to the total mass of the powder (I). In one embodiment, the amount of spinel may be 1.5 to 37% by mass, 1.5 to 35% by mass, 1.5 to 30% by mass, 2.0 to 30% by mass, or 2.0 to 29% by mass relative to the total mass of the powder (I). When blended into a resin, from the viewpoint of easily obtaining a resin composition with a lower viscosity, the amount of spinel may be more than 1% by mass and less than 29% by mass, or more than 1.0% by mass and less than 20% by mass relative to the total mass of the powder (I).
[0040] In the past, the surface of magnesium oxide particles was coated with an inorganic metal oxide powder containing spinel to improve the moisture resistance of magnesium oxide powder (for example, the above-mentioned patent documents 1 to 2, etc.). The present inventors have found that in the powder (I) containing coated particles (X), by controlling the amount of spinel contained in the coating layer within a certain range and also setting the median particle size (Di50) of the powder (I) within a certain range, a magnesium oxide powder having not only excellent moisture resistance but also a lower dielectric loss tangent can be obtained.
[0041] In addition, whether the powder (I) of the present embodiment contains coated particles (X) can be confirmed by observing the powder (I) using a scanning electron microscope, etc. In addition, the amount of spinel in the powder (I) can be confirmed by measuring the X-ray diffraction pattern of the powder (I) using an X-ray diffraction device, etc. For example, it can be measured using the following method.
[0042] <Method for measuring the amount of spinel>
[0043] The X-ray diffraction pattern of the powder (I) is measured under the following measurement conditions using a sample horizontal multifunctional X-ray diffractometer (eg, manufactured by Rigaku Corporation, product name "RINT-Ultima IV") as a measuring apparatus.
[0044] X-ray source: CuKα
[0045] Tube voltage: 40kV
[0046] Tube current: 40mA
[0047] Scanning speed: 10.0° / min
[0048] 2θ scanning range: 10°~80°
[0049] In addition, quantitative analysis of the crystal phase is performed by Rietveld analysis of the obtained X-ray diffraction pattern. Specifically, Rietveld method software (e.g., MDI, product name "Comprehensive Powder X-ray Software Jade + 9.6") is used. In addition, the calculation of the proportion (mass %) of the spinel crystal phase can be performed using an ICDD card (number: 01-075-1796).
[0050] In one embodiment, the coating layer (B) may also contain components other than spinel. As components other than spinel, there can be listed: inorganic metal oxides or inorganic metal composite oxides (except spinel) containing at least one element selected from titanium, aluminum, magnesium, silicon and calcium. Specifically, there can be listed: magnesium silicate (Mg2SiO4), magnesium ferrite (Fe2MgO4), magnesium titanate (MgTiO3), aluminum oxide (Al2O3), MgO-Al2O3 composite oxides, SiO2 and MgO-SiO2 composite oxides, etc. The coating layer (B) may also contain one or more of these inorganic metal oxides or inorganic metal composite oxides. From the viewpoint of easily obtaining a powder (I) with better moisture resistance, the coating layer (B) may also be composed only of spinel. In addition, the proportion of components other than spinel in the powder (I) can also be calculated using the same method as the determination of the aforementioned spinel amount.
[0051] The coated particles (X) are particles in which a portion of the surface of the core particle (A) is coated with a coating layer (B). From the viewpoint of easily achieving high moisture resistance and low dielectric loss tangent, the coated particles (X) are preferably core-shell particles in which the entire surface of the core particle (A) is coated with a coating layer (B). In addition, the so-called "core-shell particles" refer to coated particles in which most of the surface of the core particle (A) is coated. Regarding whether the coated particle (X) is a core-shell particle, for example, in a cross-sectional image of the coated particle (X) obtained by a field emission scanning electron microscope (for example, manufactured by Carl Zeiss, product name "MERLIN, FE-SEM") and an energy dispersive X-ray spectrometer (for example, manufactured by Bruker, product name "QUANTAX system XFlash 6 / 60SDD, EDS"), when the ratio (rc / ra) of the cross-sectional perimeter ra of the core particle (A) to the perimeter rc of the portion of the cross section of the core particle (A) coated by the coating layer (B) is 0.6 or more, it can be judged that most of the core particle (A) is coated by the coating layer (B) (i.e., it is a core-shell particle).
[0052] In one embodiment, the proportion of coated particles (X) in the powder (I) is preferably 80% or more, more preferably 90% or more. Powder (I) may contain particles (other particles) other than coated particles (X) within the range of the spinel amount and median particle size (Di50) of the powder (I) of the present embodiment that can maintain the physical properties. Other particles include: uncoated core particles (A), particles of inorganic metal oxides or inorganic metal composite oxides (for example, alumina particles, silica particles, spinel particles), etc. These may contain one species alone or two or more species. In addition, particles of inorganic metal oxides or inorganic metal composite oxides may also be particles added during manufacture as a coating component of the core particles (A).
[0053] In one embodiment, the powder (I) may contain only coated particles (X) or only core-shell particles as coated particles (X). The proportion of coated particles (X) in the powder (I) can be calculated, for example, by observing the powder (I) using the aforementioned field emission scanning electron microscope (FE-SEM) and energy dispersive X-ray spectroscopy (EDS), and the degree of coated particles (X) present in the 50 particles measured. For example, when observing any 50 particles in the aforementioned region, if all 50 particles are coated particles (X), the proportion of coated particles (X) in the powder (I) can be regarded as 100%.
[0054] In one embodiment, the thickness of the coating layer (B) in the coated particle (X) can be 40 μm or less, or 35 μm or less, from the viewpoint of easily maintaining high thermal conductivity. When filled in a resin, from the viewpoint of easily obtaining a resin composition with lower viscosity and good fluidity, it can be 30 μm or less, or 26 μm or less. In addition, the thickness of the coating layer (B) can be a value calculated from the difference between the median particle size (Da50) of the raw material powder constituting the core particle (A) and the median particle size (Di50) of the powder (I) finally obtained during the manufacture of the powder (I) of the present embodiment, or it can be a value measured using a scanning electron microscope.
[0055] Figure 1 This is an example of a photograph obtained by observing the powder (I) of this embodiment using a field emission scanning electron microscope (FE-SEM) and energy dispersive X-ray spectroscopy (EDS). Figure 1 , it can be confirmed that the powder (I) contains the coated particles (X). The powder (I) of this embodiment containing such coated particles (X) has better moisture resistance and is easy to achieve a low dielectric loss tangent.
[0056] <Median Particle Size (Di50) of Magnesium Oxide Powder (I)>
[0057] The median particle size (Di50) of the powder (I) of the present embodiment is greater than 25 μm and less than 180 μm. The powder (I) of the present embodiment can take into account both high moisture resistance and low dielectric loss tangent by having a ratio of spinel to the total mass of the powder (I) within the aforementioned range and a median particle size (Di50) of 25 to 180 μm. In one embodiment, the median particle size (Di50) of the powder (I) can also be 25 to 170 μm, 30 to 170 μm, or 30 to 150 μm. In addition, in this specification, the so-called "median particle size (D50)" refers to the average particle size (D50) of 50% in the volume-based particle size distribution using a laser diffraction light scattering method. The cumulative particle size distribution is represented by a distribution curve in which the horizontal axis is the particle size (μm) and the vertical axis is the cumulative value (%). Specifically, it can be measured under the following conditions.
[0058] (Method for determining median particle size (Di50))
[0059] The median particle size (Di50) of the powder (I) is determined by measuring the volume-based particle size distribution using a laser diffraction particle size distribution measuring device (e.g., Beckman Coulter (KK) product name "LS13 320", Microtrac Bell (KK) product name "MT3300EXII", etc.). Specifically, a 50 cm glass beaker is filled with 3 0.1 g of the powder (I) and 0.1 g of pure water are mixed with an ultrasonic homogenizer (e.g., Microtech Nition (Co., Ltd.), product name "Smurt NR-50M (Titanium alloy blade) (NS-50M-MT3))")) was dispersed for 60 seconds. The dispersion of the powder (I) subjected to the dispersion treatment was added drop by drop using a dropper to the aforementioned laser diffraction particle size distribution measuring device, and the measurement was performed 30 seconds after the addition of a prescribed amount. In addition, the refractive index of water was set to 1.33, and the refractive index of the powder (I) was set to 1.74.
[0060] In one embodiment, from the viewpoint of easily achieving high moisture resistance and low dielectric loss tangent, the BET specific surface area (Si) of the powder (I) may be less than 2.7 m 2 / g, also 2.1m 2 / g or less, also 1.9m 2 From the viewpoint of improving the fluidity when filling in the resin, the range may be 0.01 to 2.1 m / g. 2 / g, or 0.05~1.9m 2 / g. In addition, the BET specific surface area can be measured by the following method.
[0061] (Measurement method of BET specific surface area (Si))
[0062] In a measuring tank of a fully automatic specific surface area measuring device (e.g., manufactured by Mountech, product name "Macsorb HMmodel-1201", BET one-point method), 5 g of powder (I) is filled and the specific surface area is measured. The degassing conditions before the measurement can be set to 200° C. and 10 minutes. In addition, helium and nitrogen (mixed concentration: 30.5%) can be used as carrier gas and adsorption gas, respectively.
[0063] In one embodiment, the average circularity (ARi) of the powder (I) may be 0.75 or more, 0.80 or more, 0.85 or more, or 0.90 or more. If the average circularity (ARi) of the powder (I) is 0.75 or more, it is easy to become a magnesium oxide powder with a lower dielectric loss tangent. In addition, the average circularity (ARi) of the powder (I) can be measured using the following method.
[0064] (Method for measuring average circularity (ARi))
[0065] After fixing the powder (I) with a carbon tape, osmium coating is performed. Thereafter, the particles constituting the powder (I) are photographed at a magnification of 500 to 50,000 times using a scanning electron microscope (e.g., manufactured by JEOL Ltd., product name "JSM-7001F SHL"), and the projected area (A) of the particles is calculated using an image analyzer (e.g., manufactured by Nippon Roper Ltd., product name "Image-Pro Premier Ver. 9.3"). p ) and the projected circumference (L), the circularity is calculated by the following formula (2). The circularity is calculated for any 200 particles and the average value is taken as the average circularity (ARi).
[0066] Circularity = 4πA p / L 2 ...(2)
[0067] In one embodiment, the ratio of periclase (crystallization of magnesium oxide) to the total mass of powder (I) is preferably 80% by mass or more, more preferably 85% by mass or more, and further preferably 87% by mass or more. In one embodiment, the total amount of periclase and spinel in powder (I) may also be 100% by mass. If the ratio of periclase in powder (I) is 80% by mass or more, the ratio of the components other than periclase and spinel in powder (I) will decrease, and it is easy to become a powder (I) having better moisture resistance and low dielectric loss tangent.
[0068] In one embodiment, the diameter of the periclase crystallites of powder (I) is preferably 50×10-9 m or more. If the crystallite diameter is 50×10 -9 m or more powder (I), the thermal conductivity is easy to become good. In addition, the so-called "crystal diameter" refers to the value calculated using the Scherrer formula using the X-ray diffraction method. In addition, when the particles in the powder are polycrystalline, the crystallite diameter represents the average value of the size of the single crystal in the polycrystalline.
[0069] In one embodiment, the average particle density of the powder (I) is preferably 0.1 to 7.0 g / cm 3 , more preferably 0.5 to 5.5 g / cm 3 If the average particle density is 0.1-7.0 g / cm 3 , it is easy to be uniformly dispersed in the resin, and the thermal conductivity and dielectric properties are easy to become good. In addition, the average particle density of the powder (I) can be measured by the following method.
[0070] (Method for measuring average particle density)
[0071] 2.0 g of the powder (I) is placed in a sample cell for measurement, and the average particle density is measured by a gas (helium) substitution method using a dry density meter (eg, manufactured by Shimadzu Corporation, product name "AccuPyc II 1340").
[0072] The powder (I) of this embodiment has excellent moisture resistance. In one embodiment, the magnesium hydroxide content measured under the following conditions is preferably less than 50% by mass, more preferably less than 30% by mass, and further preferably less than 10% by mass. The powder (I) of this embodiment has excellent moisture resistance and is not easy to generate magnesium hydroxide.
[0073] (Measurement conditions of magnesium hydroxide content after test)
[0074] 10 g (M1) of magnesium oxide powder (I) is allowed to stand for 168 hours in a test apparatus (e.g., ESPEC (Co., Ltd.), product name: Highly Accelerated Life Tester EHS-212M, unsaturated mode) at a temperature of 135° C. and a humidity of 85 RH%. The mass (M2) of the magnesium oxide powder (I) after standing is measured, and the change in mass before and after standing is substituted into the following formula (1) to calculate the magnesium hydroxide content.
[0075] {(M2-M1) / 18.0}×(40.3 / M1)×100...(1)
[0076] (In formula (1), M1 is the mass (g) of the magnesium oxide powder (I) before standing, M2 is the mass (g) of the magnesium oxide powder (I) after standing, and 18.0 and 40.3 are the molecular weights of H2O and MgO, respectively.)
[0077] In one embodiment, the viscosity of the powder (I) measured under the following conditions is preferably 2000 Pa·s / 25°C or less, more preferably 1000 Pa·s / 25°C or less, and further preferably 500 Pa·s / 25°C or less. The powder (I) of this embodiment is a powder containing particles with relatively good surface smoothness, so the fluidity when filled in the resin is also likely to be good.
[0078] (Viscosity measurement conditions)
[0079] A resin composition containing 60% by volume of a bisphenol A type liquid epoxy resin (epoxy equivalent: 184 to 194, for example, manufactured by Mitsubishi Chemical Corporation, product name "JER828") and 40% by volume of a powder (I) was subjected to flow measurement using a rotational rheometer at a shear rate of 1.0 / s and a plate shape of a circular flat plate. The viscosity was measured at a sample thickness of 1 mm and a temperature of 25 ± 1 °C.
[0080] In one embodiment, from the viewpoint of making the filling property and fluidity of the resin better, the powder (I) can also be surface treated with a surface treatment agent. In addition, the polar functional groups on the particle surfaces constituting the powder become easy to reduce, and it is easy to achieve a lower dielectric loss tangent. As a surface treatment agent, silane coupling agents, aluminate coupling agents, etc. can be listed. These can be used alone or in combination with more than two kinds. Among these, from the viewpoint of easily reducing the polar functional groups on the particle surfaces, it is preferably treated with a silane coupling agent, and more preferably silazanes such as hexamethyldisilazane (HMDS), vinyltrimethoxysilane, etc. have a vinyl silane coupling agent. In addition, for powder (I) with or without surface treatment, for example, it can be confirmed by analyzing the powder using IR, TG-DTA, mass spectrometry, etc.
[0081] In one embodiment, the thermal conductivity of the powder (I) measured under the following conditions may be 4.0 to 8.0 W / mK, or 5.0 to 7.0 W / mK. The powder (I) of this embodiment has excellent moisture resistance, can achieve a low dielectric loss tangent, and can easily maintain high thermal conductivity.
[0082] (Measurement conditions of thermal conductivity)
[0083] Powder (I) and spherical alumina powder (e.g., manufactured by Denka Corporation, product name "DAW-07", product name "ASFP-40", etc.) are mixed in a volume ratio of 51:49 to prepare a mixed powder. The mixed powder is filled in a silicone resin (e.g., manufactured by Shin-Etsu Chemical Co., Ltd., product name "SE1885:A", product name "SE1885:B", etc.) so that the ratio of the mixed powder becomes 77.5% by volume to prepare an evaluation sheet. The evaluation sheet is measured using a thermal resistance measuring machine (e.g., manufactured by Hitachi Technical Service Co., Ltd., product name "TRM-046RHHT") to determine the thermal conductivity.
[0084] In one embodiment, the dielectric loss tangent of a resin sheet containing the powder (I) (a sheet formed of a polyethylene resin and the powder (I). The ratio of the powder (I) in the resin sheet is 20% by volume) measured under the conditions described below at 36 GHz is preferably 4.0×10 -4 Below, more preferably 3.5×10 -4 Below, more preferably 3.0×10 -4 In addition, the "dielectric loss tangent" refers to the filler-converted dielectric loss tangent (tanδ f ).
[0085] tanδ c =V f tanδ f +(1-V f )·tanδ r ...(3)
[0086] In formula (3), V f Indicates filler content (mass %), tanδ c Represents the dielectric loss tangent of the resin sheet, tanδ r Indicates the dielectric loss tangent of polyethylene resin (PE).
[0087] As described above, the powder (I) of the present embodiment has excellent moisture resistance and can achieve a low dielectric loss tangent that can also be applied to high-frequency band equipment. The reason why the powder (I) of the present embodiment can achieve a low dielectric loss tangent is that the total amount of polar functional groups can be reduced by reducing the particle surface area, and the OH groups and surface adsorbed water can be reduced by introducing the spinel layer.
[0088] [Method for producing magnesium oxide powder (I)]
[0089] The magnesium oxide powder (I) of the present embodiment can be produced, for example, by a method comprising a step (step (1)) of coating a raw material powder containing magnesium oxide with a coating component containing aluminum and then calcining the raw material powder. An embodiment of the method for producing the powder (I) comprising the step (1) will be described below.
[0090] <Step (1)>
[0091] In the production method of this embodiment, step (1) is to coat the raw material powder containing magnesium oxide with the coating component containing aluminum and then sinter the raw material powder. Here, the "raw material powder" refers to the core particles (A) containing magnesium oxide as a main component.
[0092] (Raw material powder)
[0093] In one embodiment, the median particle size (Da50) of the raw material powder is preferably 10 to 150 μm from the viewpoint of easily controlling the median particle size (Di50) of the obtained powder (I) within the range of 25 to 180 μm. The aforementioned median particle size (Da50) may also be 15 to 150 μm, 20 to 140 μm, or 40 to 130 μm. If the median particle size (Da50) of the raw material powder is within the aforementioned range, it becomes easy to obtain magnesium oxide powder (I) having a low dielectric loss tangent.
[0094] In one embodiment, the average circularity (ARa) of the raw material powder may be greater than 0.70, greater than 0.80, or greater than 0.90 from the viewpoint of easily improving the filling property of the resin. In addition, the average circularity (ARa) of the raw material powder can be measured by the same method as the average circularity (ARi) of the aforementioned powder (I). In one embodiment, the average circularity (ARi) of the powder (I) may be greater than 1.0, or greater than 1.05, relative to the average circularity (ARa) of the raw material powder (ARa) ((ARi) / (ARa)). If (ARi) / (ARa) is greater than 1.0, it becomes easy to uniformly form a coating layer, and the surface irregularities of the particles constituting the powder (I) tend to become smaller.
[0095] In one embodiment, the BET specific surface area (Sa) of the raw material powder may be 0.01 to 20 m 2 / g, or 0.01~10m 2 / g, can also be 0.01~1m 2 / g. The BET specific surface area (Sa) of the raw material powder can also be measured by the same method as that of the powder (I). In one embodiment, the BET specific surface area (Si) of the powder (I) relative to the BET specific surface area (Sa) of the raw material powder ((Si) / (Sa)) can be 5.0 or less. If (Si) / (Sa) is 5.0 or less, when the obtained powder (I) is filled in a resin, the fluidity and filling properties are easily improved.
[0096] The method for preparing the raw material powder is not particularly limited, and for example, the raw material powder may be prepared by calcining magnesium hydroxide powder.
[0097] In the raw material powder, from the viewpoint of reducing the dielectric loss tangent and the reliability of the electronic material, it is preferred that the impurities of alkali metal elements such as Li, Na and K, metal elements such as Fe, and Cl - Br - Specifically, the total amount of these impurities and anions in the raw material powder is preferably 0.01 mass % or less.
[0098] (covering method)
[0099] In the manufacturing method of this embodiment, there is no particular limitation on the method for coating the raw material powder, and for example, a vibrating mixer, a flame melting method, a stirring fluidized bed coating, etc. can be used. Among them, from the viewpoints that it is easy to control the amount of spinel in the obtained powder (I) and it is easier to control the BET specific surface area (Si) and the average roundness (ARi), it is preferred to coat the raw material powder by a stirring fluidized bed coating.
[0100] (Stirred fluidized bed coating)
[0101] In one embodiment, step (1) may include the step of spraying a slurry containing an aluminum-containing coating component onto the raw material powder to perform a stirred fluidized bed coating. In addition, stirred fluidized bed coating, also known as tumbling fluidized bed coating, tumbling fluidized granulation coating, etc., is a coating method using a coating device with a blade rotor mounted at the bottom of a general fluidized bed device. As the aluminum-containing coating component, an inorganic metal oxide powder (B1) containing aluminum oxide powder is preferred. The inorganic metal oxide powder (B1) may also contain other powders besides aluminum oxide powder, for example, silicon dioxide powder, etc. In a preferred embodiment, the ratio ((Db150) / (Da50)) of the median particle size (Db150) of the inorganic metal oxide powder (B1) to the median particle size (Da50) of the raw material powder may be 8.0×10 -6 ~1.0×10 -1 , or 5.0×10 -5 ~5.0×10 -2When (Db150) / (Da50) is within the above range, the surface of the raw material powder can be easily and efficiently coated.
[0102] In one embodiment, the proportion of the aluminum-containing coating component in the slurry can be 0.1 to 80 mass % or 1 to 50 mass % relative to the total mass of the slurry from the viewpoint of easily adjusting the amount of spinel contained in the obtained powder (I) to more than 1 mass % and less than 38 mass %.
[0103] In one embodiment, the dispersion medium contained in the slurry preferably contains water or ethanol, and more preferably contains water. In addition, the slurry may also contain components other than the coating component and the dispersion medium. As other components, for example, dispersants, binders, etc. can be listed. These other components can contain one alone, or two or more can be used in combination.
[0104] In one embodiment, the amount of the coating component containing aluminum relative to the raw material powder is preferably 1 to 25% by mass relative to the total amount (100% by mass) of the raw material powder and the coating component containing aluminum, from the viewpoint of easily adjusting the amount of spinel contained in the obtained powder (I) to more than 1% by mass and less than 38% by mass. That is, when the raw material powder is coated by agitated fluidized bed coating, the slurry can be sprayed onto the raw material powder in a range of 1 to 25% by mass of the ratio of the coating component containing aluminum relative to the total amount (100% by mass) of the raw material powder and the coating component containing aluminum. In other embodiments, the amount of the coating component sprayed relative to the aforementioned total amount may also be 1% by mass or more and less than 25% by mass, 1 to 20% by mass, 1% by mass or more and less than 20% by mass, or 1 to 18% by mass.
[0105] In one embodiment, the stirred fluidized bed coating can be carried out at 20 to 150° C., 30 to 100° C., or 50 to 90° C. In addition, the coating time is not particularly limited as long as the surface of the raw material powder is sufficiently coated. From the viewpoint of easily forming a uniform coating layer (B), it can be 0.01 to 24 hours, 0.05 to 24 hours, or 0.1 to 12 hours.
[0106] The agitated fluidized bed coating can be performed using a conventionally known agitated fluidized bed apparatus, for example, a product name "Turning Fluidized Granulation Coating Apparatus MP (Multiplex)" manufactured by Powrex Corporation can be used.
[0107] <Firing>
[0108] In the manufacturing method of the present embodiment, step (1) includes a step of sintering after coating the raw material powder. As the sintering temperature, from the viewpoint of easily forming a uniform coating layer (B), it is preferably 500 to 1600°C, more preferably 700 to 1600°C, further preferably 1000 to 1600°C, and particularly preferably 1000 to 1400°C. In one embodiment, it may also exceed 1000°C and be below 1600°C. In addition, with regard to the sintering time, from the viewpoint of easily forming a uniform coating layer (B), it is preferably 0.5 to 10 hours, and more preferably 1 to 8 hours.
[0109] <Other Processes>
[0110] After step (1), the powder (I) obtained may sometimes become an agglomerate. Therefore, a pulverization process may be performed as required. As a pulverization method, it is preferably carried out under conditions where the BET specific surface area (Si) of the powder (I) is not easily changed, for example, a mortar, a bead mill, a ball mill, etc. can be used.
[0111] Furthermore, the process may include a step of surface treating the obtained powder (I) with a surface treatment agent, a washing step for reducing impurities (for example, the aforementioned anions, etc.) in the powder (I), and the like.
[0112] In one embodiment, after the raw material powder is calcined, the obtained powder (I) may be classified by sieving, wind classification, etc. By classifying the powder (I), it becomes easy to control the median particle size (Di50), BET specific surface area (Si), etc. of the powder (I) within a suitable range.
[0113] [use]
[0114] The powder (I) of the present embodiment has excellent moisture resistance, and when filled in resin, can achieve low dielectric loss tangent that can also be applied in high-frequency band equipment. Therefore, the powder (I) of the present embodiment can be suitable for use as a resin filling material, especially can be suitable for use as a filling material for the resin combination used in the high-frequency band equipment sealing material. Other embodiments of powder (I) are the use of an inorganic filler as a sealing material for high-frequency band equipment or its method of use. Here, "high-frequency band equipment" can also be a mobile phone or a car loading component utilizing high-frequency band radio waves.
[0115] [Resin composition]
[0116] The resin composition of the present embodiment contains the magnesium oxide powder (I) and at least one resin selected from thermoplastic resins and thermosetting resins.
[0117] The content of the powder (I) in the resin combination is not particularly limited and can be appropriately adjusted as required. In addition, the powder (I) of the present embodiment also has good fluidity when filled in the resin, so in order to obtain desired dielectric properties, the blending amount of the powder in the resin combination can be arbitrarily adjusted. For example, when used in high-frequency band substrate materials, insulating material purposes, relative to the gross mass of the resin combination, can be blended in the range of 1 to 99 mass %, more preferably in the range of 10 to 90 mass %.
[0118] <Resin>
[0119] The resin composition of the present embodiment contains at least one resin selected from thermoplastic resins and thermosetting resins. More specifically, polyethylene resins, polypropylene resins, epoxy resins, silicone resins, phenolic resins, melamine resins, urea resins, unsaturated polyester resins, fluororesins, polyimide resins, polyamide-imide resins, polyetherimide resins, and other polyamide-based resins, polyester-based resins such as polybutylene terephthalate resins and polyethylene terephthalate resins, polyphenylene sulfide resins, fully aromatic polyester resins, polysulfone resins, liquid crystal polymer resins, polyethersulfone resins, polycarbonate resins, maleimide-modified resins, ABS resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins, hydrocarbon-based elastomer resins, polyphenylene ether resins, aromatic polyene-based resins, etc. These can be used alone or in combination of two or more.
[0120] The resin composition of the present embodiment may contain a curing agent, a curing accelerator, a release agent, a coupling agent, a colorant, a flame retardant, an ion scavenger, and the like within a range not inhibiting the effects of the present invention.
[0121] <Method for producing resin composition>
[0122] The manufacturing method of the resin composition is not particularly limited, and can be manufactured by stirring, dissolving, mixing, and dispersing a predetermined amount of each material. The devices for mixing, stirring, and dispersing these mixtures are not particularly limited, and a grinder, a three-roll mill, a ball mill, a planetary mixer, etc. equipped with a stirring and heating device can be used. In addition, these devices can also be used in appropriate combination.
[0123] As described above, the resin composition containing magnesium oxide powder of the present embodiment has excellent moisture resistance and can achieve a low dielectric loss tangent. In addition, the resin composition containing magnesium oxide powder of the present embodiment has excellent processability and handling properties due to its low viscosity.
[0124] Example
[0125] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to the following description.
[0126] [Example 1]
[0127] Magnesium oxide powder (manufactured by Denka Corporation, trade name "DMG-50", median particle size (Da50): 50 μm, BET specific surface area (Sa): 0.2 m 2 / g, average roundness (ARa): 0.93) as raw material powder, and alumina powder (Cabot specialty chemicals ink, product name "CAB-O-SPERSE PG008", median particle size (Db i 50): 100nm) as a slurry of the coating component is sprayed onto the raw material powder and subjected to agitated fluidized bed coating. The slurry is sprayed onto the magnesium oxide powder in an amount in which the ratio of the coating component to the total amount (100% by mass) of the magnesium oxide powder and the coating component is 5% by mass (95% by mass of magnesium oxide powder, 5% by mass of the coating component (converted into alumina powder)). Thereafter, the magnesium oxide powder (I) is obtained by calcining at 1000°C for 1 hour. The spinel amount, periclase amount, BET specific surface area (Si), the presence or absence of coated particles (X), the median particle size (Di50) and the average roundness (ARi) of the magnesium oxide powder (I) are measured under the following conditions. In addition, the physical properties of the raw material powder and the alumina powder are also the values measured under the following conditions. The results are shown in Table 1.
[0128] <Method for Determining the Amount of Spinel in Powder (I)>
[0129] The X-ray diffraction pattern of the powder (I) was measured under the following measurement conditions using a sample horizontal multifunctional X-ray diffractometer (manufactured by Rigaku Corporation, product name: "RINT-Ultima IV") as a measurement apparatus.
[0130] X-ray source: CuKα
[0131] Tube voltage: 40kV
[0132] Tube current: 40mA
[0133] Scanning speed: 10.0° / min
[0134] 2θ scanning range: 10°~80°
[0135] In addition, the quantitative analysis of the crystal phase was performed by Rietveld analysis of the obtained X-ray diffraction pattern. Specifically, the analysis was performed using Rietveld method software (manufactured by MDI, product name "Comprehensive Powder X-ray Software Jade+9.6"). In addition, the ICDD card (number: 01-075-1796) was used to calculate the proportion (mass %) of the spinel crystal phase.
[0136] <Method for Determining the Amount of Periclite in Powder (I)>
[0137] The X-ray diffraction pattern of the powder (I) was measured under the following measurement conditions using a sample horizontal multifunctional X-ray diffractometer (manufactured by Rigaku Corporation, product name: "RINT-Ultima IV") as a measurement apparatus.
[0138] X-ray source: CuKα
[0139] Tube voltage: 40kV
[0140] Tube current: 40mA
[0141] Scanning speed: 10.0° / min
[0142] 2θ scanning range: 10°~80°
[0143] In addition, the quantitative analysis of the crystal phase was performed by Rietveld analysis of the obtained X-ray diffraction pattern. Specifically, the analysis was performed using Rietveld method software (manufactured by MDI, product name "Comprehensive Powder X-ray Software Jade+9.6"). In addition, the ICDD card (number: 00-045-0946) was used to calculate the ratio (mass %) of the periclase crystal phase.
[0144] <Method for measuring median particle size (Di50) of powder (I)>
[0145] The median particle size (D50) of each material was determined by volume-based particle size distribution measurement using a laser diffraction particle size distribution analyzer (manufactured by Beckman Coulter, Inc., product name "LS13 320"). 3 of pure water and 0.1 g of the raw material powder (or powder (I)) were mixed with an ultrasonic homogenizer (Microtech Nition (Co., Ltd.), product name "Smurt NR-50M (Titanium Alloy Blade) (NS-50M-MT3))")) was dispersed at an output of 25 W for 60 seconds. The dispersion of the raw material powder (or powder (I)) that had been dispersed was added drop by drop to the laser diffraction particle size distribution measuring device using a dropper, and the measurement was performed 30 seconds after the addition of a specified amount. In addition, the refractive index of water was set to 1.33, and the refractive index of powder (I) was set to 1.74. The median particle size (D50) was calculated from the particle size corresponding to 50% of the cumulative value in the volume-based cumulative particle size distribution of the measured particle size.
[0146] <Method for measuring BET specific surface area (Si) of powder (I)>
[0147] 5 g of powder (I) was filled into the measuring tank of a fully automatic specific surface area measuring device (BET one-point method) (Macsorb HM model-1201 fully automatic specific surface area measuring device manufactured by Mountech) and the specific surface area was measured. The degassing conditions before the measurement were set to 200°C and 10 minutes. In addition, helium and nitrogen (mixed concentration: 30.5%) were used as carrier gas and adsorption gas, respectively.
[0148] <Presence or absence of coated particles (X) and core-shell particles>
[0149] The powder (I) was observed by a scanning electron microscope (manufactured by JEOL Ltd., product name "JSM-7001F") and the presence or absence of coated particles (X) was confirmed. In addition, for the powder (I), the cross-sectional perimeter ra of the coated particles in the cross-sectional image obtained by field emission scanning electron microscope (manufactured by Carl Zeiss, product name "MERLIN, FE-SEM") and energy dispersive X-ray spectroscopy (manufactured by Bruker, product name "QUANTAX system XFlash6 / 60SDD, EDS") was calculated to determine the ratio (rc / ra) of the perimeter rc of the portion coated by the coating layer (B) in the cross section of the coated particles to confirm the presence or absence of core-shell particles. At this time, the measurement was carried out at an image acquisition magnification of 1000 times, a voltage of 10 kV, a current of 500 nA, and a measurement time of 30 seconds, and elemental imaging was performed for aluminum and magnesium. In addition, image analysis was performed using ImageJ. For one particle image, the perimeter of the magnesium component image portion that would become the core portion was set to ra, and the perimeter of the portion of the surrounding portion of the magnesium component that was connected to the aluminum component that would become the shell portion (when only one pixel outside the surrounding portion of the magnesium was the mapping portion of the aluminum component, it was judged to be "connected") was set to rc, and rc / ra was calculated. Those with rc / ra of 0.6 or more were judged to be core-shell particles. The results are shown in Table 1.
[0150] <Method for measuring average circularity (ARi)>
[0151] After the magnesium oxide powder (I) was fixed with a carbon tape, osmium coating was performed. Subsequently, a scanning electron microscope (manufactured by JEOL Ltd., product name "JSM-7001F SHL") was used to photograph the particles constituting the powder (I) at a magnification of 500 to 50,000 times, and an image analyzer (manufactured by Nippon Roper Co., Ltd., product name "Image-Pro Premier Ver. 9.3") was used to calculate the projected area (A) of the particles. p ) and the projected circumference (L), the circularity is calculated by the following formula (2). The circularity is calculated for any 200 particles and the average value is taken as the average circularity (ARi).
[0152] Circularity = 4πA p / L 2 ...(2)
[0153] Next, the moisture resistance and dielectric loss tangent of the obtained powder (I) were evaluated under the following conditions. In addition, thermal conductivity and fluidity were also evaluated. The results are shown in Table 1.
[0154] <Moisture resistance evaluation>
[0155] The moisture resistance test of the powder (I) was carried out under the following conditions, and the magnesium hydroxide content after the test was measured. In addition, the evaluation was carried out according to the following evaluation criteria.
[0156] 10 g (M1) of magnesium oxide powder (I) was left to stand for 168 hours in a test apparatus (manufactured by ESPEC (Co., Ltd.), with a temperature of 135°C and a humidity of 85 RH%; product name: "Highly Accelerated Life Tester EHS-212M". The condition was unsaturated mode). The mass (M2) of the magnesium oxide powder (I) after standing was measured, and the change in mass before and after standing was substituted into the following formula (1) to calculate the magnesium hydroxide content.
[0157] {(M2-M1) / 18.0}×(40.3 / M1)×100...(1)
[0158] (In formula (1), M1 is the mass (g) of the magnesium oxide powder (I) before standing, M2 is the mass (g) of the magnesium oxide powder (I) after standing, and 18.0 and 40.3 are the molecular weights of H2O and MgO, respectively.)
[0159] (Evaluation Criteria)
[0160] Good: The rate of change to magnesium hydroxide is less than 10% by mass.
[0161] Good: The rate of change to magnesium hydroxide is 10% by mass or more and less than 30% by mass.
[0162] The rate of change to magnesium hydroxide may be 30% by mass or more and less than 50% by mass.
[0163] No: The rate of change to magnesium hydroxide is 50% by mass or more.
[0164] <Evaluation of Dielectric Loss Tangent>
[0165] Powder (I) and polyethylene resin powder (manufactured by Sumitomo Seika Chemicals Co., Ltd., trade name "FLO-THENE (registered trademark) UF-20S") were weighed in such a manner that the filling amount of powder (I) became 20% by volume, and a vibrating mixer (manufactured by Resodyn Co., Ltd.) was used to mix at an acceleration of 60G and a processing time of 2 minutes to obtain a resin composition. The obtained resin composition was put into a metal frame with a diameter of 3 cm in an amount having a thickness of about 0.3 mm, and was sheeted at 140°C, 5 minutes, and 30,000 N using a nanoimprint device (manufactured by SCIVAX Co., Ltd., trade name "X-300"). The obtained sheet was cut into a size of 1.5 cm × 1.5 cm to obtain an evaluation sample.
[0166] Next, a 36 GHz cavity resonator (Samtech (Co., Ltd.)) was connected to a vector network analyzer (Keysight Technologies, product name "85107"), and the evaluation sample was configured to plug the hole with a diameter of 10 mm set in the cavity resonator, and the resonant frequency (f0) and the unloaded Q value (Qu) were measured. The evaluation sample was rotated 60 degrees for each measurement, and the same measurement was repeated 5 times. The average value of the obtained f0 and Qu values was set as the measured value, and the dielectric loss tangent (tan δ) was calculated by the following formula (3) using the analysis software (Samtech (Co., Ltd.) software). f ). The measurement was performed under the conditions of a measurement temperature of 20° C. and a humidity of 60% RH. The obtained dielectric loss tangent value was evaluated according to the following evaluation criteria.
[0167] tanδ c =V f tanδ f +(1-V f )·tanδ r ...(3)
[0168] (In formula (3), V f Indicates filler content (mass %), tanδ c Represents the dielectric loss tangent of the resin sheet, tanδ r Indicates the dielectric loss tangent of polyethylene resin (PE).
[0169] (Evaluation Criteria)
[0170] Excellent: Dielectric loss tangent is 3.0×10 -4 the following.
[0171] Good: Dielectric loss tangent exceeds 3.0×10 -4 and 3.5×10 -4 the following.
[0172] Yes: Dielectric loss tangent exceeds 3.5×10 -4 and 4.0×10 -4 the following.
[0173] Not allowed: Dielectric loss tangent exceeds 4.0×10 -4 .
[0174] <Thermal conductivity evaluation>
[0175] Magnesium oxide powder and spherical alumina powder (a mixture of product name "DAW-07" and product name "ASFP-40" manufactured by Denka Corporation. (DAW-07) / (ASFP-40)=70 / 30 (volume ratio)) are mixed in a volume ratio of 51:49 to prepare a mixed powder. The mixed powder is filled in a silicone resin (a mixture of product name "SE1885:A" and product name "SE1885:B" manufactured by Shin-Etsu Chemical Co., Ltd.. (SE1885:A) / (SE1885:B)=50 / 50 (volume ratio)) in such a manner that the ratio of the mixed powder becomes 77.5% by volume, and mixed using a mixer with a stirring blade to obtain a resin composition. The resin composition is formed using a sheet coater to obtain a sheet for evaluation having a thickness of 3 mm. The evaluation sheet was measured using a thermal resistance measuring machine (manufactured by Hitachi Technical Service Co., Ltd., product name "TRM-046RHHT") to determine the thermal conductivity. The measurement was performed in a load fixed mode with a set load of 2 N. The evaluation was performed according to the following evaluation criteria, and a B rating or higher was considered acceptable.
[0176] (Evaluation Criteria)
[0177] Advantage: Thermal conductivity exceeds 6.0W / mK.
[0178] Good: The thermal conductivity is more than 4.0 W / mK and not more than 6.0 W / mK.
[0179] No: Thermal conductivity is 4.0W / mK or less.
[0180] <Liquidity Evaluation>
[0181] 60% by volume of a bisphenol A type liquid epoxy resin (epoxy equivalent: 184-194. Mitsubishi Chemical (Co., Ltd.), product name "JER828") and 40% by volume of powder (I) were mixed and kneaded using a planetary mixer (Thinky (Co., Ltd.), product name "Awatori Rentaro (registered trademark) AR-250", rotation speed 2000 rpm) to prepare a resin composition. Next, the shear viscosity of the obtained resin composition at 25°C was measured under the following conditions using a rotational rheometer (Anton Paar, product name "MCR-302").
[0182] Plate shape: round flat plate
[0183] Sample thickness: 1mm
[0184] Temperature: 25±1℃
[0185] Speed: 1.0 / s
[0186] The obtained viscosity was evaluated according to the following evaluation criteria, and a rating of C or higher was considered acceptable.
[0187] Good: The viscosity of the resin composition is 500 Pa·s / 25°C or less.
[0188] Good: The viscosity of the resin composition exceeds 500 Pa·s / 25°C and is 1000 Pa·s / 25°C or less.
[0189] The viscosity of the resin composition may be more than 1000 Pa·s / 25°C and not more than 2000 Pa·s / 25°C.
[0190] Not allowed: The viscosity of the resin composition exceeds 2000 Pa·s / 25°C.
[0191] [Examples 2 to 8 and Comparative Examples 1 to 6]
[0192] The raw material powder and manufacturing conditions are set as shown in Table 1. In addition, the powder (I) is prepared in the same manner as in Example 1. For the powder (I) of each example, the spinel amount, periclase amount, BET specific surface area, presence or absence of coated particles (X), median particle size (Di50) and average roundness (ARi) are measured under the same conditions as in Example 1. In addition, moisture resistance, dielectric loss tangent, fluidity and thermal conductivity are evaluated under the same conditions as in Example 1. The results are shown in Table 1.
[0193] In addition, the raw materials used in each example are as follows.
[0194] <Raw Material Powder (Core Particles (A))>
[0195] DMG50: magnesium oxide powder (manufactured by Denka Corporation, median particle size (Da50): 50 μm, BET specific surface area (Sa): 0.2 m 2 / g, average roundness (ARa): 0.93).
[0196] DMG120: magnesium oxide powder (manufactured by Denka Corporation, median particle size (Da50): 120 μm, BET specific surface area (Sa): 0.1 m 2 / g, average roundness (ARa): 0.94).
[0197] COOLMAG: magnesium oxide powder (produced by Dataihao Chemical Co., Ltd., median particle size (Da50): 10.4 μm, BET specific surface area (Sa): 0.3 m 2 / g, average roundness (ARa): 0.84).
[0198] <Coating ingredient>
[0199] Al2O3 powder: Cabot specialty chemicals ink, product name "PG008", median particle size (Db i 50):100nm.
[0200] Table 1
[0201]
[0202] As shown in Table 1, the powders (I) of Examples 1 to 8 satisfying the constitution of the present embodiment have excellent moisture resistance and can achieve a low dielectric loss tangent. In addition, the fluidity and thermal conductivity are also good. On the other hand, Comparative Example 1 in which the median particle size (Di50) of the powder (I) is less than 25 μm, Comparative Example 2 in which the proportion of spinel in the powder (I) is 0% by mass, Comparative Examples 4 to 5 in which the proportion of spinel in the powder (I) is 1% by mass, and Comparative Example 6 in which the median particle size (Di50) exceeds 180 μm have poor moisture resistance and high dielectric loss tangent values. Comparative Example 3 in which the proportion of spinel in the powder (I) is 38% by mass has good moisture resistance, but a high dielectric loss tangent. In addition, the dielectric loss tangent value of the uncoated magnesium oxide powder not containing the coated particles (X) measured by the above method is 6.7×10 -4 . The powders (I) of Examples 1 to 8 can achieve a low dielectric loss tangent compared to the uncoated magnesium oxide powder. From the above results, it can be confirmed that the powder (I) of this embodiment has excellent moisture resistance and can achieve a low dielectric loss tangent. The dielectric loss tangent of the powder (I) of this embodiment is a value that can be fully used as a filler for high-frequency band equipment.
[0203] Industrial Applicability
[0204] The powder (I) of this embodiment has excellent moisture resistance and can achieve a low dielectric loss tangent when filled in a resin. Therefore, the powder (I) of this embodiment and a resin composition using the same can be used as a ceramic filler for high-frequency band devices.
Claims
1. A magnesium oxide powder (I) comprising coated particles (X), wherein the coated particles (X) are obtained by coating the surface of a core particle (A) containing magnesium oxide with a coating layer (B) containing MgAl2O4, The ratio of MgAl2O4 to the total mass of the magnesium oxide powder (I) is more than 1 mass % and less than 38 mass %, The median particle size (Di50) of the magnesium oxide powder (I) is 25 μm or more and 180 μm or less.
2. The magnesium oxide powder (I) according to claim 1, wherein The ratio of periclase to the total mass of the magnesium oxide powder (I) is 80 mass % or more.
3. The magnesium oxide powder (I) according to claim 1 or 2, wherein The average circularity (ARi) of the magnesium oxide powder (I) is 0.75 or more.
4. The magnesium oxide powder (I) according to claim 1 or 2, wherein The magnesium hydroxide content after the test measured under the following conditions is less than 50% by mass; Determination conditions: 10 g (M1) of magnesium oxide powder (I) was allowed to stand for 168 hours in a test apparatus at a temperature of 135° C. and a humidity of 85 RH%; the mass (M2) of the magnesium oxide powder (I) after standing was measured, and the change in mass before and after standing was substituted into the following formula (1) to calculate the magnesium hydroxide content; {(M2-M1) / 18.0}×(40.3 / M1)×100...(1) In formula (1), M1 is the mass (g) of the magnesium oxide powder (I) before standing, M2 is the mass (g) of the magnesium oxide powder (I) after standing, and 18.0 and 40.3 are the molecular weights of H2O and MgO, respectively.
5. The magnesium oxide powder (I) according to claim 1 or 2, wherein The viscosity measured under the following conditions is less than 2000 Pa·s / 25°C; Determination conditions: A resin composition consisting of 60% by volume of a bisphenol A type liquid epoxy resin (epoxy equivalent: 184-194) and 40% by volume of magnesium oxide powder (I) was subjected to a rotational rheometer at a shear rate of 1.0 / s and a plate shape of a circular flat plate. The viscosity was measured at a sample thickness of 1 mm and a temperature of 25 ± 1 °C.
6. The magnesium oxide powder (I) according to claim 1 or 2, which is used for resin filling.
7. A resin composition comprising the magnesium oxide powder (I) according to claim 1 or 2 and at least one resin selected from thermoplastic resins and thermosetting resins.
8. The resin composition according to claim 7, which is used for a sealing material, a TIM material or a substrate of a high-frequency band device.
Citation Information
Patent Citations
Composite mgo powder and production thereof
JP1988248716A